Design and Synthesis of Oligoamide‐Based Double α‐Helix Mimetics. Issue 17 (23rd May 2013) - Kulikov, Oleg V.; Thompson, Sam; Xu, Hai; Incarvito, Christopher D.; Scott, Richard T. W.; Saraogi, Ishu; Nevola, Laura; Hamilton, Andrew D.
Abstract: An extensive series of bis‐oligobenzamides and bis‐oligopyridylamides have been efficiently prepared and studied by X‐ray analysis and computational methods. A modular synthesis led to double α‐helix mimics bearing between two and ten branched side‐chains. The inter‐helix angle and distance can be tuned by varying the length and rigidity of the spacer, thereby reproducing the recognition domains of a range of super‐secondary structures. Abstract : We report the modular synthesis of bis‐oligobenzamides and bis‐oligopyridylamides as double‐helix peptidomimetics with a variety of spacers in which the disposition of strands is tuneable to mimic a range of super‐secondary structures.